2014
DOI: 10.1186/1471-2296-15-104
|View full text |Cite
|
Sign up to set email alerts
|

Safety relevant knowledge of orally anticoagulated patients without self-monitoring: a baseline survey in primary care

Abstract: BackgroundEffective and safe management of oral anticoagulant treatment (OAT) requires a high level of patient knowledge and adherence. The aim of this study was to assess patient knowledge about OAT and factors associated with patient knowledge.MethodsThis is a baseline survey of a cluster-randomized controlled trial in 22 general practices with an educational intervention for patients or their caregivers. We assessed knowledge about general information on OAT and key facts regarding nutrition, drug-interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 28 publications
3
18
0
7
Order By: Relevance
“…It is likely deficits in knowledge and understanding of warfarin therapy for all participants are underestimated, self-report notwithstanding 24. The largest study until now by Chenot et al ,24 evaluating safety-relevant knowledge of patients on warfarin found substantial gaps between how the patients rated themselves and actual measured knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely deficits in knowledge and understanding of warfarin therapy for all participants are underestimated, self-report notwithstanding 24. The largest study until now by Chenot et al ,24 evaluating safety-relevant knowledge of patients on warfarin found substantial gaps between how the patients rated themselves and actual measured knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study until now by Chenot et al ,24 evaluating safety-relevant knowledge of patients on warfarin found substantial gaps between how the patients rated themselves and actual measured knowledge. For example, while almost all patients (95%) knew why they were on warfarin, 80% did not know which non-prescription analgesic was safe to take with warfarin, and 68% did not know they had warfarin-related dietary restrictions or considerations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subgroup analysis of the AFTER study including 631 individuals aged 75 and older, the rate of anticoagulant use was only 37%, and effective international normalized ratios (INR) levels were reached in only 38% . The optimal management of individuals taking OACs requires that they have a high level of knowledge and adherence, and previous studies have shown that older age is significantly associated with lower levels of knowledge about OAC therapy …”
mentioning
confidence: 99%
“…7 The optimal management of individuals taking OACs requires that they have a high level of knowledge and adherence, and previous studies have shown that older age is significantly associated with lower levels of knowledge about OAC therapy. 8 The Awareness, Efficacy, Safety, and Time in Therapeutic Range of Warfarin in the Turkish Population (WARFARIN-TR) study was a multicenter prospective study of 4,987 Turkish individuals with AF using warfarin. 6 That study revealed that older age was associated with less awareness of warfarin; 35% of individuals aged 80 and older were aware of warfarin.…”
mentioning
confidence: 99%